Nilai-Nilai Pendidikan Karakter dalam Novel Merindu Cahaya de Amstel Karya Arumi Ekawati - Insi, Regina; Khoiri, Qolbi; Effendi, Hamdan (Edusia: Jurnal Ilmiah Pendidikan Asia, 2022)
This research aims to identify and explain the values of character education in the novel Merindu Cahaya de Amstel by Arumi Ekowati. This research is library research (library research). The research data is in the form of character education values in the novel Merindu Cahaya de Amstel, with the data source being the Novel Merindu Cahaya de Amstel by Arumi Ekowati. The data collection technique that the author uses in this research is the documentation method. Meanwhile, data analysis uses content analysis. This research shows that in the novel Merindu Cahaya de Amstel, there are character education values , including religious values, likes to read, independence, hard work, creativity, and tolerance. The relevance of character education values in teenagers today can be found in family, school, and community life.